Streptomyces marincola sp. nov., a Novel Marine Actinomycete, and Its Biosynthetic Potential of Bioactive Natural Products - Shi, Songbiao; Cui, Linqing; Zhang, Kun; Zeng, Qi; Li, Qinglian; Ma, Liang; Long, Lijuan; Tian, Xinpeng (Frontiers in Microbiology, 2022)
Marine actinomycetes are an important source of antibiotics, but many of them have yet to be explored in terms of taxonomy and functions. In this study, two marine actinobacterial strains, designated SCSIO 64649T and SCSIO 03032, were isolated from the ocean. Phylogenetic analysis of the 16S rRNA gene sequences showed that strain SCSIO 64649T formed a single clade with SCSIO 03032 (similarity 99.5%) and sister clades with the validly published species Streptomyces specialis DSM 41924T (97.1%) and Streptomyces manganisoli MK44T (96.8%). The whole genome size of strain SCSIO 64649T was 6.63 Mbp with G + C content of 73.6%. The average nucleotide identity (ANI), digital DNA-DNA hybridization (dDDH) and the average amino acid identity (AAI) between strain SCSIO 64649T and its closest related known species were well below the thresholds recommended for species delineation. According to the results of polyphasic taxonomy analysis, these two isolates are proposed to represent a novel species in genus Streptomyces with the name Streptomyces marincola sp. nov. Strains SCSIO 64649T and 03032 contain 37 putative biosynthetic gene clusters (BGCs), including polyketide synthase (PKS), non-ribosomal peptides synthase (NRPS), ribosomally-synthesised and post-translationally modified peptides (RiPPs), indole, guanidinotides, ectoine, melanin, terpene, siderophore and phenazine. In silico analysis revealed that this new species has the great potential to produce a series of special novel natural products, such as the novel polyene polyketides compound, two mayamycin analogs, series of RiPPs, etc. Significant bioactive natural products, such as heronamide F, pieicidin A1, and spiroindimicin A, were also detected in SCSIO 64649T. Metabolic crude extract of this new species showed strong antimicrobial activity. This study demonstrated that the novel species Streptomyces marincola is a valuable source of new bioactive secondary metabolites and the potential were evaluated based on genomes mining, compound detection and antimicrobial activities.